Analysing the Efficacy of Customary Arbitration for Settlement of Land Disputes in Nigeria - Olorunfemi, John Funsho; Ibe, Kingsley; Omale, Godwin Musa (ABUAD Law Journal, 2021)
A number of cases in court with respect to the recognition and enforcement of customary arbitration awards relate to land disputes. Customary arbitration awards and the resort to traditional oath taking seem to be one of the ways by which title to land is established, particularly under customary law. The courts in Nigeria have been very active on the resolution of land disputes even after the conduct of customary arbitration. This is probably due to the uncertainty emanating from whether a customary arbitration award can be deemed to be final, binding or enforceable where a party decides to reject the award. Relevant judicial decisions however show that the perceived confusion or uncertainty over the efficacy of customary arbitral award is lack of understanding of the peculiar facts and decision in each case. This article adopts the doctrinal research methodology by relying mainly on relevant judicial decisions and literature to analyze the efficacy of customary arbitration as a dispute resolution mechanism for settlement of land dispute in Nigeria. It finds that a customary arbitration award estops another party from reiterating the same issue in court.